Autoimmune Bullous Disease in Childhood - (:unkn) unknown (MEDKNOW PUBLICATIONS & MEDIA PVT LTD, 2017)
Background: Autoimmune bullous disorders (AIBDs) are a heterogeneous group of diseases which are rarely seen in children. Studies concerning the immunobullous diseases in pediatric patients are scarce. Aims and Objectives: In this study, we aimed to investigate the clinical features and treatment outcomes of AIBDs in children. Materials and Methods: The electronic records of the patients in our AIBDs outpatient clinic were retrospectively reviewed. All cases diagnosed before the age of 16 years were included in the analysis of clinical features, treatment outcomes, and follow-up data. Results: Of the 196 patients with immunobullous diseases, 9 (4.6%) were diagnosed before the age of 16 years. Mean age of the patients at the time of diagnosis was 7.72 +/- 5.66 years. Among nine patients, linear immunoglobulin A disease (LAD), pemphigus vulgaris (PV), and bullous pemphigoid (BP) were seen in 5, 2, and 2 children, respectively. All patients were treated with at least two systemic agents (including methylprednisolone, dapsone, methotrexate, salazopyrine, intravenous Ig [IVIg], and rituximab) leading to clinical remission in all of them after a mean period of 31.77 +/- 27.99 months. Conclusion: In line with earlier studies, LAD was the most common immunobullous disease and in general, associated with a favorable response to dapsone. This study was noteworthy in that the patients with PV and BP demonstrated a relatively more recalcitrant course, requiring rituximab and IVIg for remission, respectively. Overall, patients had a good prognosis.
Keywords: Autoimmune bullous disease; bullous pemphigoid; childhood; linear immunoglobulin; A disease; pemphigus vulgaris; OF-THE-LITERATURE; PEMPHIGUS-VULGARIS; JUVENILE PEMPHIGUS; OUTCOMES; TUNISIA